1988
DOI: 10.1109/8.1178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of random errors in planar near-field measurement

Abstract: A bstract-Expressions which relate the signal-to-noise ratio in the near field to the signal-to-noise ratio (WN) in the far field are developed. The expressions are then used to predict errors in far-field patterns obtained from near-field data. A technique to measure the noise in the far-field pattern is also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 2 publications
0
14
0
2
Order By: Relevance
“…Synthesized-reference-wave holography was proposed in a PhD thesis [21] where several aspects were thoroughly analyzed (these methods allow utilizing the advantages of methods for probe compensation of amplitude and phase near-field measurements for planar and cylindrical scanning [1][2][3][4][5][6][7][8][9][10][11][12], including accuracy analyses). Most of the results have been published [22][23][24][25][26][27][28], such as a description of holographic near-field measurements using probe compensation for planar and cylindrical scanning, a comparison of holographic near-field and far-field measurements with and without probe compensation, accuracy analyses using mathematical models considering random processes with correlation intervals, numerical simulations considering random errors as well as deterministic errors, and processing of measurement statistics.…”
Section: Ieee Antennas and Propagation Magazine Vol 50 No 5 Octomentioning
confidence: 99%
“…Synthesized-reference-wave holography was proposed in a PhD thesis [21] where several aspects were thoroughly analyzed (these methods allow utilizing the advantages of methods for probe compensation of amplitude and phase near-field measurements for planar and cylindrical scanning [1][2][3][4][5][6][7][8][9][10][11][12], including accuracy analyses). Most of the results have been published [22][23][24][25][26][27][28], such as a description of holographic near-field measurements using probe compensation for planar and cylindrical scanning, a comparison of holographic near-field and far-field measurements with and without probe compensation, accuracy analyses using mathematical models considering random processes with correlation intervals, numerical simulations considering random errors as well as deterministic errors, and processing of measurement statistics.…”
Section: Ieee Antennas and Propagation Magazine Vol 50 No 5 Octomentioning
confidence: 99%
“…The measurements (see below) indicated that the longitudinal z-position errors with u~~10-3 were the most important. The variances can be calculated using Equation (6). Assuming (see [8]) that ci = 2/N = 1/32 , the values shown in Figures 4 and 5 by dots were obtained.…”
Section: -Iso -Isomentioning
confidence: 99%
“…If the individual errors are considered to be independent errors and ct ,c2 «1, then [8,19] aB(Kl,K2)0"1 The variances of the angular spectra are given by Equation (6). The individual terms, a B(j~and aq(j~, are given by Equations (7) and (8).…”
Section: Accuracy Analysesmentioning
confidence: 99%
See 2 more Smart Citations